Sifat Organoleptik, Sifat Fisik dan Daya Terima Sosis Ayam dengan Penambahan Tepung Kulit Pisang Kepok (Musa paradisiacal linn) sebagai Filler Sumber Serat - Putri Indah Kirani; Aaf Falahudin; Lili Adam Yuliandri (Tropical Livestock Science Journal, 2026)
This study aims to analyze the organoleptic properties, physical properties and acceptability of chicken sausages added with kepok banana peel flour (Musa Paradisiacal Linn) (TKP) as a fiber source filler, and to obtain the best balance of sausages added with kepok banana peel flour. This study was conducted experimentally using a Completely Randomized Design (CRD). The treatments given were in the form of additions (TKP) of 5 levels, namely: P0: 100% wheat flour + 0% TKP (as control),; P1: 95% wheat flour + 5% TKP; P2: 90% wheat flour + 10% TKP; P3: 85% wheat flour + 15% TKP; P4: 80% wheat flour + 20% TKP. Each treatment was repeated 4 times. The variables observed were physical properties (tenderness), organoleptic (color, taste, texture, and aroma) and acceptability. The data obtained were analyzed by ANOVA. The analysis results showed that the addition of TKP had a significant effect (P<0.05) on all tested parameters, except aroma (P>0.05). The highest taste value was found in the 5% TKP treatment (3.60 ± 0.23). Tenderness increased significantly in the 5% and 15% TKP treatments (4.00 ± 1.25 and 4.00 ± 0.00), indicating that TKP was able to increase the tenderness of the sausage. A significant decrease in color value occurred with increasing TKP concentration, where the darkest color was found in the 20% TKP treatment (1.45 ± 0.21). The highest acceptability was recorded in the 5% TKP treatment (4.00 ± 0.12) indices a potential high level of consumer acceptance. Based on these results, it can be concluded that the addition of TKP up to 5% is the best treatment to produce chicken sausages with the most preferred physical, organoleptic and acceptability properties.